Pengaruh Aerasi Injeksi Udara terhadap Beberapa Parameter Kualitas Air di Lokasi Budidaya Ikan Waduk Ir. H. Djuanda - Lismining Pujiyani Astuti; Niken TM Pratiwi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2016)
Waste of fish farming in floating net are fish feces, urine and undigested feed which is one source of organic matter inputs in Ir. H. Djuanda. Waste organic materials can cause eutrophication of waters. Air injection is one way aeration to increase oxygen to help the process of organic matter decomposition. The purpose of this study was to assess the effect of air injection on some parameters of water quality in fish farming side. This research was conducted at the location of fish farming Ir. H. Djuanda in June-September 2013. Injection of air using a compressor with a pressure of 3 atm as a source of air and perforated pipe at a depth of 3.6 m. Air injection carried out for 8 hours. Observation point vertically at a depth of 3.6 m and horizontally at a distance of -1.5 m (behind the diffuser pipe); 0 (the diffuser pipe); 1.5 m (right and left pipe); +1.5; +3 And +6 m (in front of the pipe diffuser) and a distance of 17 m of pipe which is control. After eight hours of aeration showed that the concentration of organic matter, free carbondioxide, N-NO2 tend to belower in cages aerated but N-NO3 concentration was higher in locations aeration cage than controls cageKeywords: air injection aeration, water quality, fish cage culture, Ir. H. Djuanda Reservoir